Simplify the radical expression. Assume that all variables represent positive real numbers. Please help ASAP! :(
![Simplify the radical expression Assume that all variables represent positive real numbers Please help ASAP class=](https://us-static.z-dn.net/files/dd7/50fd9031e8efc71ea5d848e45b6d6d3f.jpeg)
Answer:
-2a^2b^2*(cube root of (a^2)*b)
Step-by-step explanation:
Cube root of -8 = -2
a^8 = a^6 * a^2. Cube root of a^6=a^2.
b^7 = b^6 * b. Cube root of b^6=b^2.
Multiple accordingly: -2*a^2*b^2(cube root of a^2b)